(untitled) (Plant Tissue Culture and Biotechnology, 2025)
The selection of potential salinity tolerant varieties is important for the cultivation of wheat in saline prone areas. A screening was performed to assess the salt tolerance capacity of 15 wheat varieties of Bangladesh and 10 advanced lines (exotic) in a hydroponic culture system at four distinct salt concentrations (0, 12, 16, and 20 dS/m). The results revealed that different salinity levels significantly affect the growth attributes by reducing the shoot length and fresh as well as dry weight of roots and shoots, with a few exceptions in some genotypes at 12 dS/m salinity. The highest STI (Salt tolerance index) was observed in nine genotypes, namely BINA Gom-1, ESWYT P-44, ESWYT P-28, BARI Gom-23, ESWYT P-19, BARI Gom-27, BARI Gom-29, Pavon-76 and BARI Gom-32 which are regarded as tolerant varieties and advanced lines. The wheat genotypes were subjected to molecular assessment using 21 Single Sequence Repeat (SSR) markers associated with salinity tolerance. SSR marker assisted assessment identified 116 alleles in 25 wheat genotypes, with an average of 5.52 alleles per locus. In this experiment, the marker Xwmc-24 generated the highest (0.825) polymorphism information content (PIC) and Nei’s (1973) gene diversity (0.845). Twenty-five genotypes were categorized into six distinct clusters using similarity indices-based cluster analysis. Advanced lines, namely ESWYT P-44, ESWYT P-28, ESWYT P-19 and HYVs, namely BARI Gom-27 and BARI Gom-29, were grouped in cluster 5, while BINA Gom-1 was identified in cluster 1. Considering all the facts, it can be concluded that these just mentioned varieties and inbred advanced lines may be the potential candidates for breeding programs towards salinity tolerance in wheat. Plant Tissue Cult. & Biotech. 34(2): 173-191, 2024 (December)